Race and Contention in Twenty-First Century U.S. Media - Smith, Jason A.; Thakore, Bhoomi K. (Taylor & Francis, 2016)
This volume explores and clarifies the complex intersection of race and media in the contemporary United States. Due to the changing dynamics of how racial politics are played out in the contemporary US (as seen with debates of the "post-racial" society), as well as the changing dynamics of the media itself ("new vs. old" media debates), an interrogation of the role of the media and its various institutions within this area of social inquiry is necessary. Contributors contend that race in the United States is dynamic, connected to social, economic, and political structures which are continually altering themselves. The book seeks to highlight the contested space that the media provides for changing dimensions of race, examining the ways that various representations can both hinder or promote positive racial views, considering media in relation to other institutions, and moving beyond thinking of media as a passive and singular institution.